ADVANCES IN BOUNDARY LAYER FLOW AND HEAT TRANSFER - Anati Ali, 1981-, editor 490411; Abdul Rahman Mohd. Kasim, contributor 492901; Ahmad Qushairi Mohamad, 1991-, contributor 520450; Arshad Khan, contributor 218345; Ilyas Khan, contributor 529546; Asma Khalid, 1983-, contributor 604397; Mohd. Rijal Ilias, contributor 494031; Mohammed Al-Sharifi,Hussein Al, contributor 646284; Lim, Yeou Jiann, contributor 499243; Mohd. Ariff Admon, contributor 492759; Mohd. Zuki Salleh, contributor 217585; Nor Athirah Mohd. Zin, 1989-, contributor 555846; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2018)
Bibliography: page 110-114